Kepemimpinan Kepala Sekolah dalam Pengembangan Program Sekolah Satu Atap - Nokman Riyanto; Nurfuadi Nurfuadi (Journal Of Administration and Educational Management (ALIGNMENT), 2022)
This study aims to describe and analyze the principal's leadership in planning, implementing, and evaluating the development of school work programs at SMP Negeri 4 Satu Atap Karangjambu. This study uses data collected through interview, observation, and documentation studies. Data analysis techniques include data collection, data presentation to drawing conclusions. The results of the research on program planning are carried out at the beginning of each school year involving all stakeholders in the school. Program implementation refers to the timeline of plans that have been made together with collaboration between elements in the school. The principal has carried out the implementation, organization and evaluation of each program and made the evaluation a guide for the process of planning and implementing future programs. In conclusion, the leadership of the principal has a very important role in the process of developing the one-roof school program. This one-roof school principal has carried out management as well as principal leadership in an effort to develop school programs starting from planning, implementation, to program evaluation.Keywords: leadership, principal, program development, one roof school